Definition and Exploration of the Integrated CO2 Mineralization Technological Cycle - Bourgeois, Florent; Laniesse, Priscillia; Cyr, Martin; Julcour, Carine (Frontiers in Energy Research, 2020)
This paper is part of a multi-disciplinary research program on development and application of an integrated CO2 mineralization (ICM) framework for development of carbon mineralization as a CO2 mitigation solution. ICM is viewed as a three concentric layer system: technological, industrial integration and decision-making. The search for viable ICM solutions in a given societal and economic context, which could be posed as an inverse design problem, begins with the identification and characterization of every system component. As an early writing on the development and applicability of the proposed ICM framework, this contribution focuses on ICM’s inner technological layer. Several technological pathways, each one defined as a set of processing and transformation steps that connect a feedstock to a specific marketable product, can coexist within this layer. The paper addresses the characterization of one such technological pathway, whose cycle is divided into three successive blocks: feedstock, carbonation and valorization. The proposed concepts are illustrated through the valorization of ferronickel slag from New Caledonia as supplementary cementitious material or cement constituent, a case study that targets the production of “greener” construction materials. The data presented in the paper confirm the feasibility of characterizing the chosen ICM technological pathway, giving credit to the proposition that ICM can be approached as an inverse design problem. While exemplifying the significance of the characterization work necessary for one particular ICM technological pathway, the paper argues that development of ICM requires working on a scale considerably larger than that of standard mineral carbonation process research. Indeed, where grams of carbonated products are sufficient to investigate mineral carbonation processes, kilograms are mandatory to test and validate the use performance of final marketable products. Without precluding the merits of seeking innovative solutions, the authors argue that unit operations and transformation processes whose validity is proven at an industrial scale should be favored for timely development of viable ICM solutions.